แนวทางการนิเทศภายในเพื่อยกระดับผลสัมฤทธิ์ทางการเรียนของนักเรียน โรงเรียนบ้านอรุโณทัย อาเภอเชียงดาว จังหวัดเชียงใหม่ - นัยน์ปพร ปานกลัด (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study has 2 objectives which are 1) to study the conditions and problems of collegial supervision in Baanarunothai School, Chiang Dao District, Chiang Mai Province and 2) to study the guidelines for Collegial Supervision to Raise Student Learning Achievement in Baan arunothai School, Chiang Dao District, Chiang Mai Province. There are 3 procedures of this study. 1) study the conditions and problems of collegial supervision in Baan arunothai School, Chiang Dao District, Chiang Mai Province. The population used in this study were 84 teachers of Baanarunothai School in the academic year 2557. The tools used in this study was questionnaires with 5-level rating scale and the data was analyzed by using average (μ) and standard deviation (σ). 2) study and draft the guidelines for Collegial Supervision to Raise Student Learning Achievement in Baan arunothai School. The populations used in this study were administrators or involves supervision outstanding from the school’s collegial supervision under Chiang Mai Primary Educational Service Area Office 3. The tools used in this study was questionnaire and the data was analyzed by inductive inference. 3) examine the guideline of collegial supervision. The populations for this study were 7 experts and the tools used in this study was the examination form of possibility, suitability, and usefulness. The data was analyzed by using average (μ) and standard deviation (σ). ช The findings found that the conditions of collegial supervision in Baanarunothai School, Chiang Dao District, Chiang Mai Province was in the moderated level. Considering each aspect, et was found that they were at moderated level. Ranging from high level to low level were as follows : planning and project supervision, current state of collegial supervision, problems and needs for supervision, conducting the supervision and evaluating the supervision. The problem of collegial supervision in Baanarunothai School found that the data analysis based on various aspects also has a little practice and a lack of clarity, no conclusions about current state of collegial supervision, problems and needs for supervision into practice in a systematic way, no meeting planned for supervision, teachers are not involved in targeting the collegial supervision, administrator do not oversee themselves, collegial supervision was discontinue, supervisors lacked of knowledge understanding about the use media and tools for collegial supervision and lacked of information from evaluation to develop and improve operations to better supervision. The guideline of collegial supervision to Raise Student Learning Achievement in Baan arunothai School, Chiang Dao District focus on the committee responsible to clear, planed by the participation of teachers and school personnel, action supervision in a continuous calendar defined, the target of the supervisory and inform teachers and school personnel have been know clearly as well as to evaluate and report the results to teachers and school personnel have been know to take to improve development operations even further.The results of possibility, suitability and usefulness was in the highest level.